Arthropod Diversity in Organic and Non-Organic Rice Cultivation Systems - Juniaty Arruan Bulawan; Fitrianti Handayani; Agung Gema Ramadhan; Sri Ita Tarigan (Jurnal Ilmu Pertanian Indonesia, 2026)
The increasing demand for organic rice has encouraged the adoption of environmentally friendly rice cultivation systems. This study aimed to analyze arthropod diversity in rice fields managed under organic SRI and non-organic systems in Lamedai Village, Tanggetada District, Kolaka Regency, Indonesia. Arthropods were sampled using pitfall traps, yellow sticky traps, and sweep nets. The results showed that the organic SRI system supported higher arthropod abundance and diversity than the nonorganic system. A total of 1,065 arthropod individuals, representing 8 orders and 32 families, were recorded in organic SRI rice fields, whereas only 240 individuals were found in non-organic fields. These findings indicate that the organic SRI system enhances arthropod diversity and contributes to maintaining the balance of agroecosystems. Therefore, organic SRI rice cultivation has the potential to support sustainable agriculture through biodiversity conservation and improved ecosystem management in the Philippines. Keywords: Arthropod diversity in rice fields, system of rice intensification, biodiversity conservation in agriculture